Online Teaching Preparedness Among Nepali EFL Educators: Determinants unveiled - Bohara, Bhuban Bahadur (EDUTREND: Journal of Emerging Issues and Trends in Education, 2025)
This study examined the preparedness of Nepali teachers of English as a Foreign Language to teach online. It considered various factors, including demographic (gender, age, and education) and professional contexts (school location—rural vs. urban, teaching level—basic vs. secondary, employment status—permanent, temporary, relief grant quota, institutional, or school type—institutional vs. community), along with their ability to reconfigure content prepared for conventional teaching to online teaching. An online survey of 236 EFL school teachers was analyzed using SPSS 20.0, with findings presented through tables, a heat map, and bar diagrams. Results indicated that the preparedness determinants include ICT skill training, school type (institutional vs. community), school location (urban vs. rural), job nature, and academic qualification. The findings also showed training and institutional context as driving forces behind EFL teachers’ digital preparedness.